Establishing the correlation between food consumption habits of selected generation X and Y consumers in Metro Manila and preservation practices of Filipino food heritage - Padilla, Stephanie Joy B. (Animo Repository, 2022)
As a part of everyday life, the food consumption habits of Generation X and Y are not given much attention. On the other hand, the preservation practices of Filipino Food Heritage are being observed on different occasions. The main objective of this study was to establish the relationship between the two variables. This study was conducted within Metro Manila and participated in by 200 Generation X and Y respondents using a self-administered questionnaire modified from the studies of Asma et al. (2010) and Hernandez et. al (2018), and four business representatives in the form of an interview. Under the independent variable, the food consumption habits that were measured are health, mood, convenience, sensory appeal, and ethical concern; meanwhile, the preservation practices gauged were Traditional Knowledge, Local Community, Events, and Documentation. After applying the measures of central tendency and Pearson correlation, results showed an R-value of about 0.679 meaning that the factors/dimensions are significantly strong and positively correlated with one another and indicating a direct relationship. In addition, the results of the interview support the outcome of the statistical analysis. It is recommended that further research like descriptive and causal studies can be conducted to fully understand the relationship between consumption and culture.